HUBUNGAN KEKERABATAN BURUNG GELATIK JAWA (Padda oryzivora) DI PULAU JAWA BERDASARKAN KARAKTER MORFOLOGI - R. Susanti; Margareta R.; Nugroho E.K.; Lidia Martanti (The East Java Biological Society, 2008)
The study was conducted to evaluated the phylogenetics of the morphology character of gelatik jawa (Padda oryzivora). Fifty four P. oryzivora from natural population in Surabaya, Malang, Ngawi, Bekasi, Karawang, Cirebon, Bogor, Semarang, Magelang, Yogyakarta and Prambanan is adapted to condition of the research for 2 week. After individual identification card with bird ring and measured of the quantitative and qualitative of morphology characters, morphology characters of the bird were analysed of the phylogenetics. The phylogenetics of P. oryzivora population suggested that the bird from the geographic regions not a grouping. The high degree of migration is due to stress environment, especially of the broken of the forest, hunting, destroying and pesticides application. The migration of the population is due to the traffic of the trade from the region to the other region. This problem press to put the constitution into effect the trade embargo this species. The degree of the individual variation due to the degree of the migration, random breeding and selection. The degree of the inbreeding of the birds is not reported, so need to follow-up studies.